Pendidikan Androgini kepada Anak - Siusana Kweldju (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1998)
The Androgynous Education for Children. The androgynous education is a proposed educational model which fits to transformations that might occur in a society that undergoes changes from a traditional to a modern and industrial one. These changes also affect the existing values, which motivate the increasing needs of androgynous education, like the needs of double income families, educational democratization, nuclear families, which call for new balances. This model can only be put into practice with the parents’, teachers’ and societies’ support. The androgynous educational model can only be a success if there is a belief that everyone has his freedom to pursue one’s career.